Karakteristik kimia milkswit dan krimbrownswit: “inovasi produk olahan berbahan baku palm kernel oil” - Rina Ekawati; David Ahmad Fattah; Ayu Paramitha; Ilham Abdillah; Mukhsonatin Fauziyah; pipit Wijayanti (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Palm oil produces crude palm oil and palm kernel oil. Palm kernel oil can be processed into an alternative product for Milkswit and Krimbrownswit. Both processed products contain nutrients that are beneficial for health. In addition, Milkswit and Krimbrownswit can also be used as a form of diversification of processed products from palm oil. This study was aimed to identify the chemical characteristics of Milkswit and Krimbrownswit as processed products derived from palm kernel oil. This research was conducted from November 2020 – to January 2021 (3 months) at the Organic Chemistry Laboratory, Yogyakarta State University. This study was laid out in a non-factorial completely randomized design with different treatments. Milkswit used four treatments, namely: without food flavoring (A), adding food flavoring (B), adding food flavoring and cocoa powder (C), and adding food flavoring, chocolate, and milk powder (D). Krimbrownswit used two treatments, namely: without the addition of chocolate and with the addition of chocolate powder. Milkswit and Krimbrownswit treatment was repeated twice. The result showed that Milkswit products with the addition of food flavors, chocolate, and powdered milk (D) gave water, ash, total protein, and vitamin C content higher than Milkswit without the addition of food flavoring and cocoa powder. The content of vitamin C and total protein in Krimbrownswit with the addition of chocolate powder was 14.7 and 3.3 times higher, respectively than Krimbrownswit without the addition of chocolate powder. Both types of Krimbrownswit have a calorie content that accordance with the standard for the List of Food Ingredients by the Ministry of Health Republic of Indonesia and the water content has accordance with the quality standard of SNI 3541: 2014 for margarine products